Foundational Arithmetic Proficiency and Mathematics Performance Among Grade 10 Students: Predictors, Differences, and Stakeholder Perceptions - Sablan, Carlo James; Lorezo, Hanz Leo (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study investigated the relationship between foundational arithmetic proficiency and mathematics performance among Grade 10 learners at Taft National High School in Eastern Samar, Philippines. Anchored on Cognitive Load Theory, Constructivist Learning Theory, Gagné’s Hierarchical Learning Theory, Information Processing Theory, Social Cognitive Theory, and Ecological Systems Theory, the study examined how arithmetic deficiencies and selected learner variables influence mathematics achievement. A convergent parallel mixed-methods design was employed, integrating quantitative and qualitative data for comprehensive analysis. The respondents included all 271 Grade 10 learners enrolled during School Year 2025–2026, while selected students and mathematics teachers participated in interviews. Data were gathered using an adapted questionnaire, a 20-item Arithmetic Proficiency Test aligned with DepEd MELCs, students’ mathematics grades, and structured interview guides. Quantitative data were analyzed using descriptive statistics, Pearson’s Product-Moment Correlation, t-tests, and one-way ANOVA, while qualitative data were examined through thematic analysis. Findings revealed that most learners demonstrated moderate foundational arithmetic proficiency, with substantial difficulties in fractions, decimals, and integer operations. A strong and statistically significant positive relationship was found between arithmetic proficiency and mathematics performance, indicating that students with stronger arithmetic skills achieved higher mathematics grades. Significant differences in mathematics performance were observed according to economic status, attendance, section, parental involvement, and self-perceived math ability, while sex showed no significant difference. Qualitative findings further revealed that arithmetic deficiencies contributed to math anxiety, avoidance behaviors, low confidence, and instructional challenges. Teachers implemented remediation and differentiated instructional strategies, although persistent conceptual gaps remained evident among some learners. The study concluded that foundational arithmetic proficiency is a critical determinant of mathematics achievement and that mathematics learning is shaped by interconnected cognitive, emotional, motivational, and contextual factors. The study recommends targeted remediation programs, strengthened school–parent partnerships, improved attendance monitoring, and instructional practices that support learners’ self-efficacy and reduce math anxiety. This study aligns with Sustainable Development Goal (SDG) 4: Quality Education by promoting foundational numeracy and equitable mathematics learning opportunities. It also relates to SDG 10: Reduced Inequalities through its examination of socio-economic and contextual factors affecting academic achievement. The study contributes to educational and socio-economic sustainability by supporting evidence-based interventions that strengthen foundational numeracy, improve learner engagement, and promote inclusive and context-sensitive mathematics instruction in rural and semi-urban educational settings.